Compassionate engagement of communities in support of palliative and end-of-life care: challenges in post-pandemic era - Vitorino, Joel Vieira; Duarte, Beatriz Veiga; Ali, Amira Mohammed; Laranjeira, Carlos (Frontiers in Medicine, 2024)
Over the years, humanity has faced various global crises of different kinds that have caused great suffering in the community, such as wars, slavery, torture or the Holocaust, but also climate change, economic crises, or sanitary disasters. The recent pandemic posed a barrier to palliative and End-of-Life (EoL) care, as the need for physical distance made it difficult to retain essential human interactions while minimizing the risk of viral transmission. During the COVID-19 pandemic, the robustness of supportive networks (i.e., family, friends, neighbors, and community members) determined whether someone experienced a calm death at home or an unnecessary hospital admission, labeled as an ‘emergency’. In this vein, active establishment and strengthening of such networks are the foundation of compassionate community efforts. Firstly, providing both physical and emotional support to the entire network of caregivers enhances their ability to care for others and improves the overall experience of death, including the process of dying and the ensuing bereavement period. Furthermore, individuals can enhance their own physical and mental health by practicing compassion. The ability of networks to withstand and recover from physical and emotional challenges, while maintaining strong and supportive relationships among its members, depends on the health and overall well-being of those members. Therefore, we argue that active community participation and death education can strengthen a community’s capacity to assist people facing death, dying, and bereavement.